Optimalisasi Kompetensi Mahasiswa melalui Pelatihan Budidaya Jamur Tiram sebagai Bekal Penguatan Jiwa dan Kemandirian Kewirausahaan - Dewi, Dora Silvia; Zulfida, Ida; Alfarisi, Salman; Gulo, Gratia Kanisius; Hakim, Mukti; Budiwan, Diah Wiyani (JPM: Jurnal Pengabdian Masyarakat, 2026)
The oyster mushroom cultivation skills training for students is carried out as a strategic effort to equip the younger generation with technical skills and foster an entrepreneurial spirit in the agribusiness sector. This activity is motivated by the limited practical competence of students in developing economically valuable agricultural businesses, so that the need for applied training relevant to the needs of the job market and independent business opportunities. The purpose of this activity is to improve students' technical skills in oyster mushroom cultivation and foster knowledge, attitudes, and interest in agribusiness-based entrepreneurship. The implementation method includes interactive lectures, demonstrations, direct practice, and group discussions held at P4S Cendawan Eduwisata Medan. Evaluation was carried out through pre-tests and post-tests as well as observation of participant skills during the activity. The results of the training showed a significant increase in students' technical skills with an average increase of 63.2%, including the ability to create planting media, inoculation of seeds, maintenance, up to harvesting and post-harvest handling. In addition, students' knowledge and interest in entrepreneurship also increased by 54.2%. These results demonstrate that the training is effective in developing an entrepreneurial mindset and enhancing students' readiness to develop modern agricultural-based businesses, particularly oyster mushroom cultivation. Therefore, this activity plays a crucial role in developing innovative, independent, and competitive young entrepreneurs in the agribusiness sector.